2021
DOI: 10.3906/kim-2006-51
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Olea ferruginea Roylebark extracts for potential in vitro antidiabetic and anticancer effects

Abstract: Introduction Medicinal plants have been utilized to treat various ailments all over the world, although specific to every region [1]. Regarded as a natural treasurer, these sources are plentiful and can be utilized in galenical products in a safe, standardized, and effective manner with subsequent use in primary health care facilities [2]. History has revealed that humans have been benefiting from these herbal consecrations for almost 60,000 years and they can be consumed either directly or in the form of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…For instance, the therapeutic properties of olive leaves and fruits have been previously documented, including hypoglycemic and hypotensive effects (Hejrati et al 2020). Similarly, dried olive fruits have been reported to possess anti-diabetic properties (Liaqat et al 2021). In addition to being used medicinally, S. mascatense is used as fuel, wood, and fodder source in mountainous areas.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the therapeutic properties of olive leaves and fruits have been previously documented, including hypoglycemic and hypotensive effects (Hejrati et al 2020). Similarly, dried olive fruits have been reported to possess anti-diabetic properties (Liaqat et al 2021). In addition to being used medicinally, S. mascatense is used as fuel, wood, and fodder source in mountainous areas.…”
Section: Discussionmentioning
confidence: 99%
“…In this milieu, scientific investigations need time to enhance the production, oil recovery rate, and health-promoting benefits associated with wild olives ( Knoops et al, 2004 ). Even though various studies have been conducted to enhance its oil production and recovery rate but its isolated phytochemical constituents and associated health benefits have been less explored ( Gorzynik-Debicka et al, 2018 , Liaqat et al, 2021 ). Recent work by our research group has reported that ferruginan and cycloolivil isolated from Olea Ferruginea R possess anti-leishmanial and anti-bacterial properties ( Joshi, 2012 , Zafar et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%